Intercropping of Cabbage with Maize (Bangladesh Agronomy Journal, 2020)
The experiment was carried out at the research field of Agricultural Research Station, Rajbari, Dinajpur (Latitude: 25.63544, Longitude: 88.65144) during rabi season of 2016-2017 and 2017-18 under AEZ-1 to find out the suitable crop combination for higher productivity and economic return. Five different treatments were employed in the study viz. T1= Sole maize (60cm x×20cm), T2= Maize planting (75cm×x 25cm) + 1 row cabbage (50cm×50cm) T3= Maize paired row (150cm/37.5cm x 25cm) + 2 rows cabbage (50cm x×50cm) T4=Maize planting (60cm x×20cm )+1 row cabbage (60cm x×50cm), T5= Maize paired row (120cm/30cm× x 20cm) + 2 rows cabbage (60cm x 50cm) were evaluated. Maize grain yield in intercropped combination varied from 6.60-9.23 t ha-1. But the highest maize yield was recorded in Maize planting (60cm x 20cm) + 1 row cabbage (60cm x 50cm) followed by that in maize paired row (150/37.5cm × 25cm) +2 rows cabbage (50cm x×50cm), while the highest cabbage yield was recorded in maize planting (60cm x 20cm) + 1 row cabbage(60cm x 50cm) between maize. The highest maize equivalent yield was also obtained in maize planting (60cm x 20cm) + 1 row cabbage (60cm x 50cm) followed by that in maize paired row (150/37.5cm x 25cm) + 2 rows cabbage (50cm x 50cm). The highest gross return, gross margin and BCR were obtained in maize planting (60cm × 20cm) + 1 row cabbage (60cm x 50cm) followed by that in maize paired row (150/37.5cm x 25cm) +2 rows cabbage(50cm x 50cm) and the lowest in sole sowing of maize. The overall results indicated that among the intercrop combinations maize planting (60cm x 20cm) + 1 row cabbage (60cm x 50cm) and maize paired row (150/37.5cm x 25cm) +2 rows cabbage (50cm x 50cm) were found suitable for total productivity and economic return of the system.Bangladesh Agron. J. 2019, 22(1): 115-120